we know that
if point B (-2,4) lies on a circle centered at A (1,3)
then
distance AB is equal to the radius of the circle
so
step 1
find the distance AB
dAB=√[(y2-y1)²+(x2-x1)²]
dAB=√[(4-3)²+(1+2)²]------> dAB=√[1²+3²]------> √10 units
step 2
Find the equation of a circle
(x-h)²+(y-k)²=r²--------> (x-1)²+(y-3)²=10
step 3
Any point on the circle has to satisfy the equation
(x-1)²+(y-3)² = 10
We replace x and y with the given point C (4,2).
If we replace x with 4 and y with 2
we get
(4-1)² + (2-3)² = 9+1
10=10
Because both sides of the equation are equal this means that the point
C (4,2) is on the circle.
Any point that is not on the circle won't satisfy the equation.
Only points on the circle will give us the result of 10 = 10